Distributed multi-energy system state sensing method based on dual dynamic thresholds - JIANG YIXIN; LIANG ZHIHONG; XU WENQIAN; MA DAZHONG; ZHANG YUNAN; LI WEI; ZHANG JUNKAI; YANG YIWEI; XU AIDONG; ZHANG JIAMIN; SONG WANYU; HAN YIYING (2024)
The invention provides a distributed multi-energy system state sensing method based on dual dynamic thresholds, and the method comprises the steps: determining a historical covariance matrix and a real-time covariance matrix, determining a historical matrix spectrum difference value according to the historical covariance matrix, and determining a first dynamic threshold, a real-time matrix spectrum difference value is determined according to the real-time covariance matrix, a first system state of the multi-energy system is determined according to the size relation between the real-time matrix spectrum difference value and a first dynamic threshold value, and a first judgment result is obtained; determining a second system state of the multi-energy system according to a size relationship between the maximum eigenvalue of the estimated covariance and a second dynamic threshold, and obtaining a second judgment result; and under the condition that the first judgment result and the second judgment result are the